Big Data Analytics For Organizations: Challenges and Opportunities and Its Effect on International Business Education - Ali, Twana Saeed; Kaya, Tugberk (Kurdistan Journal of Applied Research, 2019)
Big Data refers to large volumes of information. This information varies from pictures, videos, texts, audios and other heterogeneous data. In recent years, the amount of such big data has exceeded the capacity of online or cloud storage systems. The amount of data collected yearly has doubled in the past years and the concern for the volume of this data has reached its Exabyte yearly range. This paper focuses on the major issues and opportunities as well as big data storage with the aid of academic tools and researches conducted earlier by scholars for big data analysis. Modern learning environment (MLE) has to be understood in order to know how it supports learning in areas of big data such as university education systems. The utilization of online resources and web pages with laptops and mobile phones need to be understood as an attempt to integrate the modern learning environment and improve teaching in international bossiness. Big data can be fine-tuned and used to create new online learning programmers. Data collected by government departments, universities and institutions could be used as a new innovative learning system such as (MLE) which has a passive and active character i.e. it can be accessed anywhere at any time. This would also help in minimizing extended classroom activities because students would have controlled access to online knowledge from their homes